The Impact of Organizational Inertia on AI Implementation - Yang, Li; Wai Yie, Leong (INTI International University, 2025)
When ChatGPT-3.5 entered the consumer-grade market, artificial intelligence (AI) technology has developed at a rapid pace and become an important driving force for the progress of human civilization. Up to now, the landscape of large AI models has gradually presented a situation of a hundred schools of thought contending, playing important roles in industries such as industry, healthcare, education, and finance. However, it is undeniable that there are structural resistances to the application of artificial intelligence technology in social, ethical, and other aspects. Therefore, this paper, from an organizational perspective, comprehensively analyzes existing literature on organizational inertia and its impact on the application of artificial intelligence, clarifying the definition and dimensions of organizational inertia as well as the impact of each dimension on the application of artificial intelligence technology. The study found that organizational inertia has six internal dimensions: structure, resources, cognition, path, routines, and culture. Moreover, through searching for studies on the impact of organizational inertia on the application of artificial intelligence, it was found that the number of relevant representative papers is relatively limited, and only the structural, resource, cognitive, and path dimensions of organizational inertia have been verified to hinder organizations' application of artificial intelligence technology, while there is a lack of research on the impact of the routines and cultural dimensions of organizational inertia on the application of artificial intelligence technology